The Validity of PPP Revisited: An Application of Non-linear Unit Root Test - Liew, Venus Khim-Sen (Munich University Library, 2003)
To this end, the validity of purchasing power parity (PPP) remains a controversial issue, as empirical evidence is inconclusive. This study provides robust empirical evidence to support the view that negligence of non-linearity may be the culprit of these contrasting findings. This paper demonstrates that the non-linear unit root test proposed by Kapetanois et al. [Journal of Econometrics, 2003, 112, pp.359-379] is able to reject unit root in 4 out of 5 cases, implying that deviations of exchange rates is mean reverting towards the PPP equilibrium values from the non-linear perspective, whereas the augmented Dickey-Fuller (ADF) test fails in 4 out of 5 cases. Thus, previous conclusions of the invalidity of PPP may be due to misleading results from the ADF test, which has low power against non-linearity.